Effects of lowering body temperature via hyperhydration, with and without glycerol ingestion and practical precooling on cycling time trial performance in hot and humid conditions - Ross, M. L.; Jeacocke, N. A.; Laursen, P. B.; Martin, D. T.; Abbiss, C. R.; Burke, L. M. (Journal of the International Society of Sports Nutrition, 2012)
Hypohydration and hyperthermia are factors that may contribute to fatigue and impairment of endurance performance. The purpose of this study was to investigate the effectiveness of combining glycerol hyperhydration and an established precooling technique on cycling time trial performance in hot environmental conditions.